2021
DOI: 10.1097/md.0000000000024543
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for positive brain CT scan in children with traumatic brain injury and GCS = 15

Abstract: It is controversial whether it is necessary to carry out head computed tomography (CT) examination for children who had a traumatic brain injury (TBI) but are conscious (Glasgow Coma Scale (GCS) = 15). The present study explored the risk/predictive factors of positive CT results in children with mild closed head injury and GCS = 15. This was a retrospective study of children (0–18 years of age) with TBI and GCS = 15 and treated at the First People's Hospital of Wenling between 06/2013 and 06/2018. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Positive findings in CT scan were seen in 50% of the cases, with skull fracture being the predominant finding, followed by epidural hematoma (EDH) in a study. [ 11 ] This was similar to our CT scan results. Another study also observed similar results with EDH and fracture hematoma as common findings on neuroimaging.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Positive findings in CT scan were seen in 50% of the cases, with skull fracture being the predominant finding, followed by epidural hematoma (EDH) in a study. [ 11 ] This was similar to our CT scan results. Another study also observed similar results with EDH and fracture hematoma as common findings on neuroimaging.…”
Section: Discussionsupporting
confidence: 91%
“…The cases were predominantly males, as seen in other studies. [ 10 , 11 ] Road traffic accident (RTA) and fall from height formed the principal mechanism of head injury in our study. Similar observations were made in other studies [ 12 - 14 ] on head injury in pediatric patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A study by Kirschen et. involved 344 patients, of which 36 (10.5%) had a hematoma on CT examination and according to Wang et al hematomas were seen in 17.6% patients [35,36]. In comparison to those results, in the study 36 out of 136 (26.47%) patients among children with head CT lesions were found to have hematoma, including 30 boys, for whom hematoma was also the most common traumatic lesion (7.8%).…”
Section: Hematomamentioning
confidence: 61%